Characteristics, management and outcomes of very preterm triplets in 19 European regions. Issue 3 (15th September 2019) - Dudenhausen, Joachim W.; Misselwitz, Björn; Piedvache, Aurelie; Maier, Rolf F.; Weber, Tom; Zeitlin, Jennifer; Schmidt, Stephan
Abstract: Objective: To describe obstetrical care and in‐hospital outcomes in very preterm triplet pregnancies in a European multiregional cohort. Methods: Data from a prospective population‐based study of very preterm births between 22 + 0 and 31 + 6 weeks of gestation in 19 regions from 11 European countries participating in the EPICE project in 2011/2012 were used to describe triplet pregnancies and compare them with twins and singletons. Results: Triplets constituted 1.1% of very preterm pregnancies (97/8851) and 3.3% of very preterm live births (258/7900); these percentages varied from 0% to 2.6% and 0% to 6% respectively across the regions. In‐hospital mortality after live birth was 12.4% and did not differ significantly from singletons or twins or by birth order. However, 28.9% of mothers with a triplet pregnancy experienced at least one neonatal death. Ninety percent of live‐born triplets were delivered by cesarean. Vaginal delivery was associated with an Apgar score of less than 7, but not with in‐hospital mortality. Conclusions: The prevalence of very preterm triplets varies across European regions. Most triplets were born by cesarean and those born vaginally had lower Apgar scores. Overall, in‐hospital mortality after live birth was similar to singletons and twins. Abstract : European very preterm triplets had similar neonatal outcomes to twins and singletons; most were delivered by cesarean; vaginal delivery was associated with lower Apgar scores.